(untitled) (Journal of the College of Basic Education, 2023)
In this research, thin films of ferric oxide Fe 2 O 3 were prepared.on bases of heated borosilicate glass at 350C, and the membranes were preparedusing the thermal chemical spraying method. Thin films were prepared with thicknessdifferent. By calculating the absorbance and permeability of these films, the coefficient of change was studied.Absorption with photon energy as a function of thickness, as well as the forbidden energy gap was calculated.for the prepared films, where it was found that increasing the thickness led to an increase in the absorption coefficient.While this increase did not significantly affect the value of the forbidden energy gap.